AGROINDUSTRI BIOFARMAKA: DIVERSIFIKASI PRODUK OLAHAN TANAMAN BERKHASIAT OBAT MENJADI JAMU DALAM KEMASAN MODERN DI KABUPATEN JEMBER - Eno, Astrino Purmanna; Iis Nur Asyiah; Imam Mudakir; Wachju Subchan (Department of Agricultural Social Economics, Faculty of Agriculture, Brawijaya University, 2025)
This study aims to explore the biopharmaceutical agroindustry in Jember Regency, especially for Djajamu Herbs business actors based on the diversification of processed medicinal plant products into jamu in modern packaging. Given the increasing public awareness of the importance of health and the use of biopharmaceutical products, this study analyzes, among others, the selection of primary raw materials, benefits and types of jamu, product design innovation, marketing strategies, and social and economic impacts on local communities. The type of research conducted was a case study using observation, interview and documentation methods from informant of biopharmaceutical business actors, namely Djajamu Herbs. The results of the study show that diversification of jamu products in modern packaging has great potential to increase the competitiveness and economy of business actors in the biopharmaceutical agroindustry sector. In addition, diversification of jamu products such as attractive and modern packaging innovations, use of social media and e-commerce platforms, understanding consumer preferences for jamu types, and good cooperation between stakeholders, the biopharmaceutical agroindustry can support business development in this field in a sustainable manner. The findings of this study provide a contribution that the diversification of processed medicinal plant products into jamu in modern packaging has great potential to improve the welfare of business sectors in the biopharmaceutical agroindustry and can maintain the sustainability of the use of medicinal plants in the era of digitalization technology 4.0.